Creating a Picture Card Game For German Vocabulary on The Topic of Quite Mobile - Sheren Triana Sianipar; Tanti Kurnia Sari (Jurnal Pustaka Cendekia Pendidikan, 2026)
This study aimed to develop a picture card game for German vocabulary level A2 on the topic of "Quite Mobile." The study was conducted in the language lab of the Foreign Languages ​​Department at Universitas Negeri Medan. The data included words, images, and simple sentences thematically linked to the lesson "Quite Mobile." The textbook "Netzwerk neu A2," pages 80–89, served as the data source. The study was based on Richey and Klein's development model, which includes the phases of planning, development, and evaluation. The results are digital picture card games created with the Wordwall application, incorporating various game formats such as flashcards, match-up, and open the box. The developed learning resource can be accessed via the following link: https://wordwall.net. The resource was reviewed by a subject matter expert and a media expert, receiving 91.6 points for content quality and 92 points for media implementation. The picture card game is flexible and can be used anytime, anywhere, via laptop or smartphone. It's an innovative and interactive learning tool that encourages active participation from learners in German lessons.